Protective effects of hydroalcoholic extract of Stachys pilifera on paracetamol-induced nephrotoxicity in female rats - Mohammad Reza Rabani; Nahid Azarmehr; Zahra Moslemi; Heibatollah Sadeghi; Hossein Amini-Khoei; Amir Hossein Doustimotlagh (Wolters Kluwer Medknow Publications, 2021)
Background and purpose: Stachys pilifera is used in traditional medicine due to its antioxidant, anti-inflammatory, and antimicrobial effects. The goal of this study was to examine the renoprotective activity of the hydroalcoholic extract of aerial parts of S. pilifera on paracetamol (PCM)-induced nephrotoxicity. Experimental approach: The Wistar female rats were randomly divided into four groups including control, PCM, S. pilifera hydroalcoholic extract (SPE), and PCM + SPE. The animals received SPE (500 mg/kg) for one week and PCM (3 g/kg) on the 6th day orally. Kidney function tests and oxidant/antioxidant markers were determined in serum and tissue homogenate, respectively. Protein and mRNA levels of TNF-α, as well as hematoxylin and eosin staining, were assessed in the kidney tissue. Findings/Results: Treatment with SPE in the PCM group significantly decreased blood urea nitrogen and creatinine against the merely PCM rats (P < 0.05). The amount of nitric oxide metabolite and superoxide dismutase activity in the group receiving SPE showed a significant increase compared to PCM rats (P < 0.05). A significant difference in TNF-α levels between the groups was not observed. Histological changes were improved in the rats treated with SPE. Conclusion and implications: Totally, our findings showed that SPE can inhibit PCM nephrotoxicity by enhancing kidney function markers, antioxidant status, and histological changes. Though, more researches are required to estimate the possible mechanism of SPE.